Impact of Perinatal Coexposure to Chlorpyrifos and a High-Fat Diet on Kisspeptin and GnRHR Presence and Reproductive Organs - Marwa Lahimer; Narimane Djekkoun; Sophian Tricotteaux-Zarqaoui; Aurélie Corona; Isabelle Lafosse; Habib Ben Ali; Mounir Ajina; Véronique Bach; Moncef Benkhalifa; Hafida Khorsi-Cauet (Toxics, 2023)
Emerging evidence has indicated the involvement of extrahypothalamic Kisspeptin and GnRHR in reproductive function. In this study, we evaluate if maternal exposure to the pesticide chlorpyrifos (CPF) and/or a high-fat diet (HFD) has an impact on the expression of Kisspeptin and GnRHR in the reproductive organs of rats’ offspring. A total of 16 pregnant rats are divided into four groups: a control group (n = 4), CPF group (4 rats exposed daily to 1/mg/kg/day), HFD group (4 rats randomly fed a 5.25 kcal/g HFD), and coexposed group (4 rats exposed to CPF and HDF). At postnatal development postnatal day (PND) 60, male and female offspring were sacrificed. The reproductive organs (ovary and testis) were removed, and histological and immunohistological analysis and in silico quantification (TissueGnostics software 6.0.1.102, TissueFAXS, HistoQuest) were applied to investigate the impact of different treatments on Kisspeptin and GnRHR expression in reproductive organs. The main outcomes of the study showed a significant decrease in rat offspring’s body weight in the CPF group from PND30 and PND60 (p < 0.05 and p < 0.01, respectively). Histological analysis showed a significant increase in the atretic follicle and abnormal testis structure with germ cell desquamation in the CPF-exposed group. The immunodetection quantification of protein shows a significant decrease in GnRHR and Kisspeptin in the HFD and CPF exposed groups, respectively, in testis rat offspring. Perinatal exposure to CPF and HFD exposure affect the reproduction function of rat offspring.